ChemInform Abstract: Chiral Surfactant‐Type Catalyst: Enantioselective Reduction of Long‐Chain Aliphatic Ketoesters in Water. Issue 37 (September 2015) - Lin, Zechao; Li, Jiahong; Huang, Qingfei; Huang, Qiuya; Wang, Qiwei; Tang, Lei; Gong, Deying; Yang, Jun; Zhu, Jin; Deng, Jingen
Abstract A rhodium complex with an amphiphilic, chiral surfactant‐type ligand is applied to the asymmetric transfer hydrogenation of long‐chained aliphatic ketoesters.